Differential predictors of intimate partner sexual coercion versus physical assault perpetration. Issue 2 (4th May 2019) - Snead, Alexandra L.; Babcock, Julia C.
ABSTRACT: The current study attempted to strengthen existing literature regarding predictors of perpetrating intimate partner sexual violence to determine if there are unique predictors of sexual violence that differentiate it from physical abuse. It was hypothesised that men's controlling, dominant and jealousy behaviours, and verbal aggression would significantly predict increased intimate partner sexual coercion and physical assault perpetration. These predictors were expected to be more predictive of sexual coercion than physical assault perpetration. Couples were recruited from the community ( N = 159) in a cross-sectional study recruiting couples with a violent male partner. Results demonstrated that men's controlling behaviour was a significant predictor of sexual coercion and physical assault perpetration and behavioural jealousy was a significant predictor of sexual coercion perpetration. No predictors studied better predicted sexual coercion more than physical assault perpetration. These findings suggest that sexual coercion may be another type of physical assault without unique predictors.